Effects of Stigma and Discrimination Reduction Trainings Conducted Under the California Mental Health Services Authority An Evaluation of Disability Rights California and Mental Health America of California Trainings - Cerully, Jennifer L. (RAND Corporation, 2015)
Describes the methods and results of a RAND evaluation of stigma and discrimination reduction trainings delivered by two program partners, Disability Rights California and Mental Health America of California.